Simplicia Characterization And Phytochemical Screening Of Secondary Metabolite Compounds Ethanol Extract Of Trembesi Leaves (Samanea saman) - Zamharira Muslim; Heti Rais Khasanah; Yopita Sari (Politeknik Kesehatan Kemenkes Jakarta II, 2021)
Trembesi plant (Samanea saman) is a plant that has the potential as traditional medicine. People in using medicinal plants often do not know the chemical content of these plants, so that in determining the amount of dosage, people only rely on experience and estimates. Research on the characterization of trembesi leaf simplicia has never been done. Research on the characterization of trembesi leaf simplicia has never been done. The purpose of this study was to determine the characteristics of trembesi leaf simplicia including specific and non-specific characteristics. The research is carried out in the form of experiments in the laboratory. The sample used is trembesi leaves. The research stages started from discovery, making simplicia, extraction, specific and non-specific characteristics. In the phytochemical test, ethanol extract of trembesi leaves was used. Data analysis used is descriptive method. Specific results showed trembesi leaf simplicia has a coarse powder form, distinctive odor, tasteless, green in color, and on microscopic results of trembesi leaf simplicia powder there is starch, fragments in the form of epidermis, water soluble extract content 11.93%, ethanol soluble essence 18, 93% and contains flavonoids, tannins, steroids and saponins. The results of non-specific characteristics are 8.07% water content, 7.91% ash content and 0.29% acid insoluble ash content.